2006
DOI: 10.5551/jat.13.149
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Combination Therapy of Benidipine Hydrochloride and Candesartan Cilexetil on Serum Lipid Metabolism and Blood Pressure in Elderly Hypertensive Patients with Type 2 Diabetes Mellitus

Abstract: The effects of combination therapy of angiotensin receptor blockers (ARBs) and a calcium antagonist, benidipine hydrochloride, on glucose and lipid metabolism and pulse pressure were studied in elderly hypertensive patients with type 2 diabetes mellitus. Twenty-five hypertensive diabetic patients aged 65 years or older, who had been receiving candesartan cilexetil, were administered benidipine hydrochloride (4 mg/day) and followed for 4 months. After 4 months, systolic and diastolic blood pressure decreased si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…On the other hand, angiotensin inhibits the meta-bolic actions of insulin via the phosphatidylinositol 3-kinase pathway 2) , resulting in insulin resistance. Angiotensin type 1 receptor (AT1R) blockers (ARBs) and angiotensin-converting enzyme inhibitors, which function as antihypertensive agents, have been reported to prevent atherosclerosis in a study using monkeys 3) , improve insulin resistance 4) , and induce a favorable lipid profile 5,6) . Besides their metabolic effect on insulin signaling, telmisartan 7,8) and irbesartan 7) , two ARBs, have been found to activate peroxisome proliferator-activated receptor (PPAR ) in cells derived from rodents and this is independent of their AT1R blocking actions.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, angiotensin inhibits the meta-bolic actions of insulin via the phosphatidylinositol 3-kinase pathway 2) , resulting in insulin resistance. Angiotensin type 1 receptor (AT1R) blockers (ARBs) and angiotensin-converting enzyme inhibitors, which function as antihypertensive agents, have been reported to prevent atherosclerosis in a study using monkeys 3) , improve insulin resistance 4) , and induce a favorable lipid profile 5,6) . Besides their metabolic effect on insulin signaling, telmisartan 7,8) and irbesartan 7) , two ARBs, have been found to activate peroxisome proliferator-activated receptor (PPAR ) in cells derived from rodents and this is independent of their AT1R blocking actions.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, candesartan–HCTZ combination was concluded as effective for the treatment of hypertension in patients with hypertension not optimally controlled with candesartan monotherapy. Also, in a smaller study of 25 elderly Japanese hypertensive patients with diabetes who received candesartan and add-on calcium chanel blocker (CCB) treatment benidipine hydrochloride and who were followed up for 4 months, Sasaki et al24 showed significant reduction in SBP and DBP after the addition of benidipine hydrochloride (from 154/91 to 139/78 mmHg; P < 0.01).…”
Section: Candesartan: Antihypertensive Efficacymentioning
confidence: 99%
“…In patients with coronary artery disease, the formation of platelet microaggregates correlates with adverse clinical outcomes 4) . The effects of hypertension treatment agents on serum lipids have been characterized 5,6) ; however, their antithrombotic properties remain to be investigated. In vitro study has shown that losartan, an angiotensin type 1 receptor blocker (ARB), can react with thromboxane A2 receptor in human platelets 7) and may possess antithrombotic properties; however, the effects on platelet aggregation among various ARBs have not been fully investigated.…”
Section: Introductionmentioning
confidence: 99%